PI3K/AKT/mTOR Signaling Pathway Is Required for JCPyV Infection in Primary Astrocytes - Michael P. Wilczek (MDPI AG, 2021)
Astrocytes are a main target of JC polyomavirus (JCPyV) in the central nervous system (CNS), where the destruction of these cells, along with oligodendrocytes, leads to the fatal disease progressive multifocal leukoencephalopathy (PML). There is no cure currently available for PML, so it is essential to discover antivirals for this aggressive disease. Additionally, the lack of a tractable in vivo models for studying JCPyV infection makes primary cells an accurate alternative for elucidating mechanisms of viral infection in the CNS. This research to better understand the signaling pathways activated in response to JCPyV infection reveals and establishes the importance of the PI3K/AKT/mTOR signaling pathway in JCPyV infection in primary human astrocytes compared to transformed cell lines. Using RNA sequencing and chemical inhibitors to target PI3K, AKT, and mTOR, we have demonstrated the importance of this signaling pathway in JCPyV infection of primary astrocytes not observed in transformed cells. Collectively, these findings illuminate the potential for repurposing drugs that are involved with inhibition of the PI3K/AKT/mTOR signaling pathway and cancer treatment as potential therapeutics for PML, caused by this neuroinvasive virus.